CNTNAP4 deficiency in dopaminergic neurons initiates parkinsonian phenotypes - Zhang, Wenlong (Theranostics, 2020)
Rationale: Contactin-associated protein-like 4 (CNTNAP4) belongs to the neurexin superfamily and has critical functions in neurological development and synaptic function. Loss of CNTNAP4 in interneurons has been linked to autism, schizophrenia, and epilepsy. CNTNAP4 is also highly enriched in dopaminergic (DA) neurons in the substantia nigra (SN), however, few studies have investigated the role of CNTNAP4 in DA neurons, and whether CNTNAP4 deficiency in DA neurons contributes to Parkinson's disease (PD) remains unclear. Methods: Effects of CNTNAP4 knockdown or overexpression on the DA MN9D cell line were assessed via Western blotting, immunocytochemistry, and RNA sequencing. An in vivo animal model, including CNTNAP4 knockout mice and stereotaxic injections of adeno-associated viral short-hairpin RNA with the tyrosine-hydroxylase promotor to silence CNTNAP4 in the SN, as well as the resulting physiological/behavioral effects, were evaluated via behavioral tests, Western blotting, immunohistochemistry, and transmission electron microscopy. Enzyme-linked immunosorbent assays (ELISAs) were performed to examine the cerebrospinal fluid (CSF) and plasma CNTNAP4 concentrations in PD patients. Results: We demonstrated that CNTNAP4 knockdown induced mitophagy and increased α-synuclein expression in MN9D cells. CNTNAP4 knockdown in the SN induced PD-like increases in SN-specific α-synuclein expression, DA neuronal degeneration, and motor dysfunction in mice. In addition, CNTNAP4 knockdown in SN-DA neurons increased autophagosomes and reduced synaptic vesicles in the SN. Furthermore, CNTNAP4 knockout mice showed movement deficits, nigral DA degeneration, and increased autophagy, which were consistent with the SN-specific knockdown model. We also found that CSF and plasma CNTNAP4 expression was increased in PD patients; in particular, plasma CNTNAP4 was increased in male PD patients compared with controls or female PD patients. Conclusion: Our findings suggest that CNTNAP4 deficiency may initiate phenotypes relevant to PD, of which we elucidated some of the underlying mechanisms.